THE EFFECTIVENESS OF ROLE PLAY METHOD IN IMPROVING STUDENTS' SPEAKING SKILL: An Experimental Study of the First Grade in a Private Senior High Schoolin Bandung - Safitri Ramadhani, - (2011)
This study is aimed at investigating whether there is a significant difference between a group that used Role Play method and a group that did not use this method, and examining students' perceptions towards the use of this method. There are some problems in learning speaking. The problems are the lack of teachers' ability and variations in teaching speaking. Besides that, the shyness of students in speaking English also becomes a problem in learning speaking. This quantitative research was conducted to the first grade of a private senior high school in Bandung academic year 2008-2009 through a true experimental design, and two classes (X1 and X2) were chosen as samples. Furthermore, the data were collected by administering speaking test and questionnaire. The results show that there was significant difference between post-test means for experimental group (M = 16.3767, SD = 2.87883) and control group (M = 12.2893, SD = 3.22527). It was supported by the t value of experimental group (t = -10.597) and large effect size (r = 0.943). The results of questionnaire also show that the students had positive perceptions about role play method. Therefore, it can be concluded that apparently, the improvement of teachers' ability and the variety of teaching methods are needed to make learning speaking more effective. Furthermore, the Role Play method is one method which can be implemented in improving students' speaking skill in senior high school.